Investigating best practices for Structure-from-Motion photogrammetry of turbid benthic environments - Savill, Kesia Louise (Curtin University, 2023)
Turbid water environments represent 8-12% of the global continental shelf regions, representing a variety of benthic habitats with high ecosystem value. The aim of this thesis is to optimise Structure-from-Motion photogrammetry in turbid benthic environments. It was found that these environments require a camera with a large sensor size and resolution, custom settings to suit the conditions, photos taken at close range, and in certain cases image enhancement, to improve the accuracy of 3D models.